PENGARUH PERSEPSI PENERIMAAN TEMAN SEBAYA TERHADAP KESEPIAN PADA REMAJA - Ajeng Triani (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstrack This research is aimed to analyze the influence of perception of peer acceptance to loneliness in adolescense. The research was conducted at Jakarta on June 2012. The population of this research are adolescences at Jakarta between 12 years old until 21 years old. Data was gathered by using scale and analyze by regression test (Anareg) using SPSS 16.0 program. The result revealed that Adjusted R Square perception of peer acceptance on loneliness was 0.051 (5.1%), which means that peer acceptance influence loneliness as much as 5.1% and the rest 94.9% influence by other factors beyond loneliness. The result of this research showed Ho is rejected and Ha is accepted, therefore the research conclusion was that perception of peer acceptance influenced loneliness toward adolescence. Keywords : Perception of Peer Acceptance, Loneliness, Adolescences, Jakarta